Analisis Kinerja Pajak Reklame Pada Badan Pengelola Pajak Dan Retribusi Daerah Kabupaten Hulu Sungai Tengah Provinsi Kalimantan Selatan - Nafis, Muhammad; Safrina, Noor; Julkawait (Indonesian Journal of Applied Accounting and Finance, 2024)
Advertising tax is a very potential source of regional income. The increase in the number of billboard installations in Hulu Sungai Tengah Regency has not been matched by strict supervision from the Government due to the detection of many cases of irregularities and fraud occurring in the field in the installation of billboards. This research aims to measure the performance of advertising taxes in Hulu Sungai Tengah Regency. The methods used are the collection ratio and the tax growth rate ratio. The results of this research show that the results of calculating advertising tax performance use ratios of average collection is 82.83% with the criteria being ineffective in achieving tax performance. Meanwhile, analysis of tax performance using the calculation of the tax growth rate ratio shows that the percentage of advertising tax performance has not succeeded in achieving performance